Pharmacokinetics of metoprolol during pregnancy and lactation. (4th December 2015) - Ryu, Rachel J.; Eyal, Sara; Easterling, Thomas R.; Caritis, Steve N.; Venkataraman, Raman; Hankins, Gary; Rytting, Erik; Thummel, Kenneth; Kelly, Edward J.; Risler, Linda; Phillips, Brian; Honaker, Matthew T.; et al.
Abstract: The objective of this study was to evaluate the steady‐state pharmacokinetics of metoprolol during pregnancy and lactation. Serial plasma, urine, and breast milk concentrations of metoprolol and its metabolite, α‐hydroxymetoprolol, were measured over 1 dosing interval in women treated with metoprolol (25–750 mg/day) during early pregnancy (n = 4), mid‐pregnancy (n = 14), and late pregnancy (n = 15), as well as postpartum (n = 9) with (n = 4) and without (n = 5) lactation. Subjects were genotyped for CYP2D6 loss‐of‐function allelic variants. Using paired analysis, mean metoprolol apparent oral clearance was significantly higher in mid‐pregnancy (361 ± 223 L/h, n = 5, P  < .05) and late pregnancy (568 ± 273 L/h, n = 8, P  < .05) compared with ≥3 months postpartum (200 ± 131 and 192 ± 98 L/h, respectively). When the comparison was limited to extensive metabolizers (EMs), metoprolol apparent oral clearance was significantly higher during both mid‐ and late pregnancy ( P  < .05). Relative infant exposure to metoprolol through breast milk was <1.0% of maternal weight‐adjusted dose (n = 3). Because of the large, pregnancy‐induced changes in metoprolol pharmacokinetics, if inadequate clinical responses are encountered, clinicians who prescribe metoprolol during pregnancy should be prepared to make aggressive changes in dosage (dose and frequency) or consider using an alternate beta‐blocker.